PENGARUH ROYALTI STREAMING MUSIK SPOTIFY, PERTUNJUKAN LANGSUNG, DAN SESSION WORK TERHADAP PENDAPATAN MUSISI INDEPENDEN - Sugihanggit, Anggraito; Noor, Iswan (Journal of Development Economic and Social Studies, 2023)
The primary source of income for independent musicians (indie) namely live performances, has decreased due to the COVID-19 pandemic. Consequently, indie musicians have started to seek alternative income sources that they can rely on, such as royalties from music streaming services like Spotify and session work. This study aims to determine the significance of the influence of Spotify music streaming service, live performances, and session work on the income of independent musicians in Malang. This quantitative research  utilizing primary data obtained from questionnaires, and analyzed using multiple linear regression analysis techniques. The results of the T-test with a significance level of <0.05 for X1 are 0.78; X2 is 0; X3 is 0.006. The result of the F-test is 23.01, and the result of the R2 test is 0.56. The findings of this study conclude that royalty from Spotify music streaming service does not have an impact on the income of independent musicians in Malang, while live performances and session work do have an influence on the income of independent musicians in Malang.